Nigeria: Country brief - HarvestPlus (International Food Policy Research Institute, 2015)
HarvestPlus improves nutrition and public health in Nigeria by promoting cassava that provides more vitamin A in the diet. We work with almost 40 partners drawn from government, business, and civil society.